Profiles of limitations in children's communicative competence: Theoretical and practical orientation for devising therapy - Dohmen, A (2009)
The complexity of communicative competence requires interventions that take pragmatic-communicative, formal-linguistic, emotional-social, cognitive and contextual aspects into account. This paper starts by outlining the range of skills and information that need to be integrated for successful communication and moves on to how these skills can be assessed to obtain a detailed profile of a child's communicative competence. Five characteristic profiles of limited communicative competence are then described. The aim of the classification is to allow for a differentiated assessment of the core problems as a basis for selecting the appropriate focus for intervention; the detection of possible underlying sources of difficulty and causal relations is not the central concern of this paper. Seven basic questions will be introduced as a guideline for intervention planning. The reader will find a set of published approaches and materials that may be useful in realising interventions to address limitations in children's communicative competence in a box on page 123.